Influência dos ajustes cardiorrespiratórios durante a respiração aérea do bagre africano (Clarias gariepinus) exposto à hipóxia - Teixeira, Mariana Teodoro [UNESP] (2014)
Air-breathing fish occur mostly in tropical regions, especially in estuaries and freshwater lakes, where the amount of dissolved oxygen is highly susceptible to fluctuations. Thus, the ecological success of these animals is particularly influenced by their physiological adjustments to detect changes in O2 levels in the water, interpret sensory information and make appropriate adjustments in their cardiorespiratory functions. Almost all air-breathing fish studied to date exhibit changes in heart rate (fH) associated with surface air breathing . It is assumed that those cardiorespiratory adjustments facilitate O2 uptake from air-breathing organ (ABO) (increased cardiac output which increases blood flow) and optimize the distribution of O2 to the tissues, increasing the efficiency of air breathing and then aerobic metabolism is maintained. In this research the cardiorespiratory parameters (fH, gill breathing frequency- fR and frequency of air breathing - fRA ) were evaluated in Clarias gariepinus for 1 hour in normoxia and then hypoxia 60 mmHg and 1 hour 1 hour in hypoxia 20 mmHg. Each animal was first submitte to this protocol (CTR), and the same was repeated after administration of propranolol (PRO) and after administration of atropine (ATR + PRO) . The fR of CTR animals in normoxia was almost constant (~ 43.16 resp.min - 1) and the two hypoxic tensions (60 and 20 mmHg) also remained stable, however we detected no significant decrease when compared to normoxia. The propranolol and atropine did not cause significant changes in fR. In CTR fish in normoxia, fRA was reduced (~ 1.85 RA.h - 1), in hypoxia 60 mmHg there were a raising and this increase was higher in hypoxia 20 mmHg . The administration of propranolol + atropine significantly change fRA compared to control only during severe hypoxia (20 mmHg). In CTR animals, during normoxia and hypoxia (60 and 20 mmHg ), the occurrence of tachycardia was observed after the RA 's. The ...